Coexistence of broad-bandwidth and strong microwave absorption in Co2+-Zr4+ co-doped barium ferrite ceramics. Issue 6 (15th April 2018) - Li, Jun; He, San; Shi, Kouzhong; Wu, You; Bai, Han; Hong, Yang; Wu, Wenjing; Meng, Qingxin; Jia, Dechang; Zhou, Zhongxiang
Abstract: BaFe12 O19 (BaM) has wide applications in electronic devices in the microwave frequency band. Ion doping has become a popular method to improve the performance of BaM in microwave absorption. This work investigates the microwave absorption properties of Ba(CoZr) x Fe12-2 x O19 (BFCZO- x, x = 0.2, 0.4, 0.6) ceramics prepared by the traditional solid-state reaction method. The structure and morphology confirm that BFCZO- x ceramics belong to the hexagonal system. The values of M s ( H c ) vary from 28 emu/g (828 Oe) to 40 emu/g (453 Oe) with the increase in x from 0.2 to 0.6, respectively. The microwave absorption results show that the maximum reflection loss can reach about −28.7 dB at 16.4 GHz of BFCZO-0.4 and present a broad bandwidth (13.34–18.8 GHz over −10 dB) with a thickness of 1.7 mm. Compared with other BaM-based materials, the coexistence of broad bandwidth and strong absorption in BFCZO- x ceramics indicates that it could be a promising material for designing microwave devices.